Development of Orthopaedic services and need of fellowship program in Nepal - Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
The term “Orthopaedics” was derived from the book Orthopédie on childhood deformity correction by Nicolas Andry in 1741. The frontispiece of the book, “Tree of Andry” has become a common logo of orthopaedic associations worldwide. Historically, western Orthopaedic and Trauma care can arbitrarily be divided into Greek and Roman period, renaissance period (14th to 17th century) and modern period. Hippocrates, the father of medicine, is credited for several techniques in orthopaedic and trauma and a lot of work was done during the renaissance period on fracture management including amputation. Hugh Owen Thomas, son of a bonesetter, who published many incredible works is considered as the father of modern orthopaedics in the UK. The use of Thomas traction splint during the First World War dramatically reduced the incidence of death due to femoral fractures and eventually, after the World War II, Orthopaedics and Trauma surgery became one of the major disciplines in medical fraternity.